Evidenciação contábil, desempenho e responsabilidade social corporativa: uma análise dos clubes de futebol brasileiros - Souza, Yasmin Maiara Torres (2023)
Soccer clubs, formerly entertainment centers, have become business segments, facing increasing pressure from society to make significant commitments to issues of public interest, often addressed through Corporate Social Responsibility (CSR) programs. In this universe, characterized by strong ties to the community and often unprofessionalized management, it is imperative to reformulate the current model in order to promote legitimacy in the eyes of society, resolve deficiencies and maintain the financial and sporting stability of clubs. In this context, the general objective of this dissertation is to analyze the relationship between accounting disclosure, performance and CSR. The research uses economic, financial, sporting and social indicators on a sample of 23 soccer clubs that competed in the A and B series of the Brazilian Championship in 2021. The period analyzed covers the years 2018 to 2022. The hypotheses were addressed through statistical techniques, using a Tobit model. Accounting disclosure, the dependent variable, was measured using a checklist related to the ITG 2003 (R1) metrics. The independent variables include economic-financial, sporting and social performance, as well as control variables. The results reveal that the adoption of CSR practices is correlated with accounting disclosure, through the number of followers on social networks and women's football teams.. However, in relation to economic-financial and sporting performance, the results suggest a positive relationship with the quality of accounting disclosure, especially when measured by general indebtedness and the club's participation in the A series. Finally, the research highlights that, unlike previous models which have only analyzed the relationship between accounting disclosure and economic, financial and sporting performance, it is crucial to understand the social context. The main contribution of this study is the application of a model that fits the reality of Brazilian soccer clubs, considering their complex interaction with society.